2019
DOI: 10.1159/000502546
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Outcomes of Community-Acquired versus Hospital-Acquired Acute Kidney Injury: A Meta-Analysis

Abstract: Background: The different clinical characteristics of community-acquired acute kidney injury (CA-AKI) versus hospital-acquired AKI (HA-AKI) have remained inconclusive, and thus, a meta-analysis was conducted to summarize and quantify the clinical significance distinguishing the 2 types of AKI. Methods: We identified observational studies reporting the clinical characteristics and prognosis of HA-AKI and CA-AKI. ORs and mean differences (MDs) were extracted for each outcome and the results aggregated. The prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 39 publications
3
28
0
1
Order By: Relevance
“…There are several limitations to our study. First, the definition of AKI depended on SCr changes in reference to patients' baseline SCr, which is not always observable (2/3 of AKI are community acquired 28 ). For patients without any SCr observed within 7 days prior to admission, we had to use their admission SCr as the baseline, which may underestimate the true AKI incidence.…”
Section: Discussionmentioning
confidence: 99%
“…There are several limitations to our study. First, the definition of AKI depended on SCr changes in reference to patients' baseline SCr, which is not always observable (2/3 of AKI are community acquired 28 ). For patients without any SCr observed within 7 days prior to admission, we had to use their admission SCr as the baseline, which may underestimate the true AKI incidence.…”
Section: Discussionmentioning
confidence: 99%
“…Fourthly, one must consider whether there are differences in the provenance of community-and hospital-acquired AKI that leads to a poorer outcome in hospital-acquired AKI patients, with iatrogenic and thrombotic disease being potential additional mechanisms in hospital-acquired AKI. Finally, pre-COVID-19 studies have shown that hospitalacquired AKI has significantly higher mortality than community-acquired AKI [18,19]. One suggested explanation was that all patients receive senior review on admission while senior review may be more sporadic during the inpatient stay.…”
Section: Discussionmentioning
confidence: 99%
“…For example, an AKI already present at the point of admission to hospital may have different pathophysiological drivers to one that occurs in a ventilated patient with a restrictive fluid management strategy. Pre-COVID-19 studies have indeed shown that risk factor profiles and outcomes are different for AKIs present on admission to hospital compared to those that develop during hospital admission [17][18][19]. We think this approach will be particularly informative in COVID-19 disease where there is a high propensity for iatrogenic kidney injury.…”
Section: Introductionmentioning
confidence: 99%
“…HA-AKI has been the focus of research over the last 2 decades; however, studies on CA-AKI have been thriving in recent years, showing that CA-AKI is as important a public health problem as HA-AKI, with a prevalence of 1.11% among adult hospitalizations, accounting for 54.4% of all AKI cases in a recent nationwide survey in China [12,13]. According to our latest meta-analysis, CA-AKI has a lower incidence of oliguria, reduced risk of ICU treatment, shorter hospital stay, and lower mortality than HA-AKI, whereas the rate of renal recovery and need for dialysis showed no significant difference between these 2 AKI subtypes [14]. Different from HA-AKI, causative factors of CA-AKI can be divided into prerenal azotemia, intrinsic renal disease and obstruction [15,16]; however, risk factors associated with renal prognosis after an episode of CA-AKI are still under debate.…”
Section: Introductionmentioning
confidence: 74%
“…Current AKI definitions and staging criteria are primarily derived from patients in the ICU, in whom the predominant spectrum of causes belongs to HA-AKI [2,6,32]. There are many differences between HA-AKI and CA-AKI with respect to epidemiology, clinical characteristics, and prognosis [14]. In this CA-AKI cohort, 70.4% (207/294) of patients had de novo intrinsic renal disease, except ATN or AIN, while only 5.1% (15/294) had a definitive previous history of chronic nephritis.…”
Section: Discussionmentioning
confidence: 99%